Monatomic nano-enzyme based on planar and axial coordination design as well as preparation and dye degradation application of monatomic nano-enzyme

By introducing oxygen atoms and axial chlorine coordination into single-atom nanoenzymes, a three-dimensional Fe-N3O-Cl activity center was constructed, which solved the problem of low catalytic efficiency of M-N4 structure, and achieved efficient dye degradation and good cycles. Usability.

CN119386912APending Publication Date: 2025-02-07SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441123.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The single-atom nanoenzymes with existing M-N4 structures have low catalytic efficiency due to their limitations in symmetry, and especially have limitations in the catalysis of certain substrates.

Method used

By introducing oxygen atoms to form an asymmetric Fe-N3O ​​planar structure and by introducing axial chlorine coordination, a three-dimensional configuration of Fe-N3O-Cl activity center is constructed, optimizing electron distribution and catalytic activity.

Benefits of technology

The catalytic activity of single-atom nanoenzymes is significantly improved, so that it exhibits efficient catalytic performance during dye degradation and has good recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386912A_ABST
    Figure CN119386912A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bionic enzymes, and discloses a monatomic nano-enzyme based on planar and axial coordination design and a preparation method thereof, and the monatomic nano-enzyme can be used for degrading dye pollutants. An active site coordination structure of hemin (Fe-N4-Cl) is inspired, oxygen atoms are innovatively introduced on the basis of a traditional Fe-N4 configuration, an asymmetric Fe-N4O plane coordination structure is formed, and the electron donor capacity of active sites is further enhanced by introducing axial chlorine coordination. The three-dimensional Fe-N3O-Cl structure active site constructed by the method obviously improves the catalytic activity. The preparation raw materials of the nano enzyme are cheap and easy to obtain, the process is simple and easy to implement, and the obtained product has a unique asymmetric coordination structure, shows extremely high peroxidase activity, can be compared favorably with a natural enzyme HRP (horse radish peroxidase), and shows wide application potential in dye pollutant treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanozymes, and specifically relates to a single-atom nanozyme based on planar and axial coordination design, and its preparation and dye degradation application. Background Art

[0002] Natural enzymes are widely used in industrial processing, disease diagnosis and treatment due to their high catalytic activity and substrate specificity. However, natural enzymes are expensive to prepare, difficult to store, have poor stability, and are very sensitive to the catalytic environment. These shortcomings limit their promotion and use in practical applications.

[0003] In order to overcome these shortcomings, artificial enzyme mimics - nanozymes have been developed. Nanozymes are a type of nanomaterials with catalytic activity similar to that of natural enzymes. They have the advantages of low cost, high stability, and easy large-scale production. They have shown broad application prospects in the fields of biosensing, environmental governance, and disease treatment. In order to further improve the performance of nanozymes, researchers began to simulate the highly evolved catalytic centers of natural enzymes at the atomic level. Single-atom nanozymes (SAzymes), as a new generation of nanozymes, have attracted much attention due to their unique catalytic activity and selectivity. In particular, single-atom nanozymes with M-N4 (transition metal-nitrogen coordination) active sites have shown excellent catalytic activity and selectivity.

[0004] However, the symmetry of the M-N4 structure limits its catalytic efficiency for certain substrates, and there is limited room for improving enzyme activity. For example, Liu et al. pointed out the limitations of the M-N4 structure in their study in Angewandte Chemie International Edition, Vol. 58, 2019, and Dong et al. in their study in Nano Research, Vol. 16, 2023.

[0005] To solve this problem, researchers have used heteroatom doping strategies to adjust the electron distribution of metal atoms, thereby optimizing the adsorption-desorption process of intermediates to improve catalytic activity. One effective method is to adjust the first coordination shell of the metal active site by replacing nitrogen atoms in the coordination shell with heteroatoms, such as forming structures such as Fe-N3S and Fe-N3P, to break the symmetrical charge distribution around the M-N4 site. However, most of this type of research focuses on two-dimensional planar structures, and the effect of heteroatom coordination in three-dimensional spatial configuration on the catalytic performance of single-atom nanozymes has not been fully studied.

[0006] Therefore, developing a single-atom nanozyme based on planar and axial coordination engineering to further improve its catalytic performance has important research significance and application value. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the present invention provides a single-atom nanozyme based on planar and axial coordination design, a preparation method thereof, and its application in dye degradation. The single-atom nanozyme has efficient catalytic ability, excellent stability, and good recyclability, thus becoming an ideal substitute for natural enzymes, especially showing broad application prospects in dye pollution treatment.

[0008] The innovative concept of the present invention is based on the following points:

[0009] The metal active center of enzymes in nature plays a core role in catalytic reactions, and the coordination environment of the metal center directly determines the rate and efficiency of the reaction. Inspired by the coordination structure of the active site of hemin chloride (Fe-N4-Cl), the present invention introduces oxygen atoms into the traditional Fe-N4 configuration catalytic site to construct an asymmetric Fe-N3O ​​planar coordination structure. In addition, axial chlorine coordination is further introduced to enhance the electron donor ability of the active site, and finally a Fe-N3O-Cl structural active center with a three-dimensional configuration is constructed.

[0010] This three-dimensional coordination structure greatly improves the electron distribution of the single-atom nanozyme and enhances its catalytic activity, making its performance in peroxidase simulation comparable to that of natural enzymes. Compared with the traditional two-dimensional Fe-N4 catalytic site, the Fe-N3O-Cl structure provides stronger electronic regulation capabilities and optimizes the adsorption and desorption behavior of reaction intermediates, thereby improving the reaction kinetic efficiency.

[0011] The single-atom nanozyme of the present invention exhibits excellent catalytic performance in the degradation process of dye pollutants, and can effectively degrade a variety of industrial dyes, such as malachite green, methyl orange, methylene blue and rhodamine B. In addition, the single-atom nanozyme can be used multiple times, showing good recycling performance, and provides an economical and efficient solution for the environmentally friendly treatment of dye wastewater.

[0012] The purpose of the present invention is achieved through the following technical solutions:

[0013] A method for preparing a single-atom nanozyme based on planar and axial coordination design, characterized in that it comprises the following steps:

[0014] (1) dispersing melamine, cyanuric acid, L-alanine and phytic acid in water, heating and stirring, adding iron salt, and freeze-drying to obtain a precursor;

[0015] (2) taking the precursor obtained in step (1), heating it to a pyrolysis temperature, cooling it, taking out the powder and grinding it to obtain Fe-N / OC SA; the pyrolysis temperature is 500 to 800°C;

[0016] (3) The Fe-N / O-C SA obtained in step (2) is dispersed in an aqueous solution of HCl, heated and stirred, filtered and washed, the precipitate is collected, and dried to obtain a single-atom nanozyme Fe-N / O / Cl-C SA.

[0017] Preferably, in step (1), the mass ratio of melamine, cyanuric acid, L-alanine and phytic acid is 1:1:1:(0.05-0.2); and the ratio of iron ions in the iron salt to L-alanine is 1 mmol:1 g.

[0018] Preferably, the iron salt in step (1) is at least one of Fe(NO3)3, Fe(NO3)3·9H2O, FeCl2, and FeCl3.

[0019] Preferably, in step (1), the stirring temperature is 50-200° C., the stirring speed is 400-800 rpm, and the time is 2-14 hours; and the freeze-drying conditions are -40-60° C., 0-10 Pa, and 30-60 hours.

[0020] Preferably, the pyrolysis in step (2) is carried out in an inert gas atmosphere, the pyrolysis temperature is 700±50°C, the heating rate is 5±3°C / min, and the pyrolysis time is not less than 2 hours.

[0021] Preferably, the concentration of the HCl aqueous solution in step (3) is 1 to 4 M, the stirring temperature is 40 to 80° C., and the stirring time is 1 to 24 hours.

[0022] The single-atom nanozyme prepared by the method of the present invention.

[0023] Application of the single-atom nanozyme of the present invention in dye degradation.

[0024] Preferably, the method comprises the following steps: mixing Fe-N / O / Cl-C SA and dye in a mass ratio of (1-10):1, and performing degradation reaction in a 1-10% H2O2 environment.

[0025] Preferably, the dye is one or more of malachite green, methyl orange, methylene blue, and rhodamine B; and the degradation reaction is carried out at pH 2 to 5 and room temperature.

[0026] Compared with the prior art, the present invention has the following improved effects:

[0027] (1) Innovatively designed catalytic active center: This invention designs Fe-N / O / Cl-C single-atom nanozymes for the first time through planar and axial coordination engineering. By introducing oxygen atoms to form an asymmetric Fe-N3O ​​planar structure and introducing axial chlorine to further enhance the electron donor ability, a three-dimensional Fe-N3O-Cl active structure is constructed. This new type of single-atom nanozyme has a clear atomic structure, which is convenient for studying the catalytic mechanism. It has a high utilization rate of metal atoms and its enzyme-like activity exceeds that of the natural enzyme HRP. Nanozymes are easy to prepare and have the advantages of recyclability and good stability, making them very suitable for practical applications.

[0028] (2) Efficient dye degradation system: Based on the peroxidase-like activity of Fe-N / O / Cl-C single-atom nanozymes, the present invention establishes a dye degradation system that can efficiently degrade dyes such as malachite green and methylene blue. Under mild reaction conditions, the nanozyme exhibits extremely high degradation efficiency, providing a new method for the treatment of dye wastewater, and has broad prospects for environmental protection and industrial applications.

[0029] The single-atom nanozyme prepared by the bionic strategy of the present invention not only exhibits efficient catalytic activity, but also has wide applicability. Its preparation method provides a reference for the future development of single-atom nanozymes, especially its application in dye degradation shows a good prospect, and has important scientific research reference value and practical application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD diagrams of Comparative Examples 1-4 are shown.

[0031] Figure 2 TEM images of Comparative Examples 1-4.

[0032] Figure 3 The XRD and Raman patterns of Example 1 and Comparative Example 1 are shown.

[0033] Figure 4 TEM and AC-HADDF-STEM images of Example 1.

[0034] Figure 5 This is the XPS graph of Example 1.

[0035] Figure 6 2 are XAFS diagrams of Example 1 and Comparative Example 1.

[0036] Figure 7 This is the evaluation of the peroxidase-like activity of Example 1.

[0037] Figure 8 The peroxidase activity comparison and electron spin resonance (EPR) experiment diagram of Example 1 and Comparative Example 1 are shown.

[0038] Fig. 9 The peroxidase enzyme kinetics of Example 1 and Comparative Example 1.

[0039] Fig.10 The degradation curve and kinetics of the dye malachite green in Example 1 are shown. DETAILED DESCRIPTION

[0040] The present invention further describes in detail the preparation process and structural characterization of single-atom nanozymes through specific examples, demonstrating the advantages of their catalytic performance and structure.

[0041] Example 1: Preparation of Fe-N / O / Cl-C single-atom nanozyme

[0042] (1) Synthesis of precursor: 2 g of melamine, 2 g of cyanuric acid, and 2 g of L-alanine were dispersed in 100 mL of deionized water with 200 μL of 50 wt% phytic acid. The suspension was vigorously stirred at 100°C with a stirring speed of 600 rpm, and 404 mg of Fe(NO3)3·9H2O was slowly added, and stirring was continued for 12 hours.

[0043] The powder was collected after freeze drying to obtain the precursor. The freeze drying conditions were -58°C and 5 Pa for 48 hours.

[0044] (2) Synthesis of Fe-N / OC single-atom nanozyme: The precursor was placed in a porcelain boat and placed in a tube furnace under argon protection. The mixture was heated to a pyrolysis temperature of 700°C at a heating rate of 5°C / min. After pyrolysis for 2 hours, the mixture was naturally cooled to room temperature. The powder was taken out and ground to obtain Fe-N / OC single-atom nanozyme.

[0045] (3) Synthesis of Fe-N / O / Cl-C single-atom nanozyme: The obtained Fe-N / OC powder was evenly dispersed in 100 mL of 3 M HCl aqueous solution and stirred at 60 °C for 9 h. After completion, the precipitate was washed with deionized water and dried to obtain Fe-N / O / Cl-C single-atom nanozyme.

[0046] Comparative Example 1: Fe-N / OC single-atom nanozyme

[0047] Referring to Example 1, the HCl heat treatment in step (3) was not performed to obtain Fe-N / OC single-atom nanozyme.

[0048] Comparative Example 2: Fe-N / OC-500 Catalyst

[0049] Referring to Comparative Example 1, the difference from Comparative Example 1 is that the pyrolysis temperature in step (2) is 500°C. Comparative Example 3: Fe-N / OC-600 catalyst

[0050] Referring to Comparative Example 1, the difference from Comparative Example 1 is that the pyrolysis temperature in step (2) is 600°C. Comparative Example 4: Fe-N / OC-800 catalyst

[0051] Referring to Comparative Example 1, the difference from Comparative Example 1 is that the pyrolysis temperature in step (2) is 800°C.

[0052] Example Effect Description

[0053] Figure 1 The XRD patterns of Comparative Examples 1-4 show that there are no obvious diffraction peaks of Fe species in these four samples, indicating that Fe may exist in the form of single atoms or as a non-crystalline coordination compound.

[0054] Figure 2 : The TEM images of Comparative Examples 1-4 show that an amorphous coordination compound of P / O-Fe is formed at a pyrolysis temperature of 500-600°C, and Fe does not exist in a single atom form. When the pyrolysis temperature is increased to 800°C, the formation of obvious Fe metal clusters is observed, while at 700°C, the TEM spectrum of Fe-N / OC does not show metal clusters or coordination compounds, indicating that Fe atoms are uniformly dispersed on the substrate.

[0055] Figure 3 :The XRD and Raman spectra of Example 1 and Comparative Example 1 show that the Fe-N / OC and Fe-NO / Cl-C samples have a characteristic peak of graphite carbon at 2θ≈24°, and no characteristic peaks of other iron species (such as iron oxide or elemental iron) are detected. In the Raman spectrum, characteristic peaks of D band and G band appear, indicating that defect-rich amorphous carbon exists in these samples.

[0056] Figure 4 : The TEM and AC-HAADF-STEM images of Example 1 show that the Fe-N / O / Cl-C catalyst does not form agglomerates or nanoparticles. The N, O, P, and Cl elements are evenly distributed, proving that the prepared nanozyme contains a large number of uniform active units. Through HAADF-STEM, it was observed that the Fe atoms are evenly distributed and anchored on the substrate in the form of single atoms, with an Fe loading of 0.54wt%.

[0057] Figure 5 : In the XPS diagram of Example 1, N1s, O1s, P2s and Cl2p are analyzed in detail respectively. The fitting of N1s shows the existence of pyridinic N, pyrrolic N and graphitic N, and pyridinic N and pyrrolic N can be used as sites for anchoring iron atoms. The Fe-O peak at 533.2eV in the O1s spectrum shows that Fe coordinates with O. The peak at 197.7eV in the Cl2p spectrum corresponds to Fe-Cl, indicating that Fe coordinates with Cl. The characteristic peak of Fe-P is not observed in the P2s spectrum, indicating that P does not directly coordinate with Fe.

[0058] Figure 6 :The XAFS spectra of Example 1 and Comparative Example 1 show that the edge front peaks of Fe-N / OC, Fe-NO / Cl-C and FePc at 7113 eV all indicate the existence of similar Fe-N4 planar structures. The fitting results of the EXAFS spectrum show that the best coordination of Fe-N / OC is Fe-N / O with a coordination number of 3.8, while the best coordination numbers of Fe-N / O / Cl-C are Fe-N / O (3.7) and Fe-Cl (0.9). This shows that the pickling treatment introduces Cl ligands, which coordinate with the Fe-N / O planar structure to form Fe-N / O / Cl-C sites.

[0059] Table 1 EXAFS fitting of different samples at Fe K-edge

[0060]

[0061]

[0062] Figure 7 :The evaluation of the peroxidase-like activity of Fe-N / O / Cl-C single-atom nanozyme was demonstrated. The results showed that Fe-N / O / Cl-C had strong oxidase (OXD) activity in the absence of H2O2, and when a small amount of H2O2 (1mM) was introduced, it exhibited strong peroxidase (POD) activity. When reacting with three typical substrates ABTS, OPD, and TMB, Fe-N / O / Cl-C showed obvious colorimetric reactions, indicating that it has good peroxidase-like activity.

[0063] Figure 8 :The peroxidase-like activities of Fe-N / O / Cl-C and Fe-N / OC were compared. After the introduction of axial Cl, the apparent activity of Fe-N / O / Cl-C was 1.69 times that of Fe-N / OC, which further verified the rationality of the design. In addition, in the electron spin resonance (EPR) experiment, the characteristic signal of ·OH radicals was observed, and the fluorescence enhancement amplitude of Fe-N / O / Cl-C was the largest, indicating that it produced more active free radicals during the catalytic process, explaining the reason for its high catalytic activity.

[0064] Table 2 Comparison of enzyme kinetics of Fe-N / OC SA, Fe-N / O / Cl-C SA and HRP

[0065]

[0066]

[0067] Fig. 9:The differences between Fe-N / O / Cl-C and Fe-N / OC in peroxidase kinetics are shown. Kinetic analysis shows that both can effectively oxidize TMB in the presence of H2O2 and follow the Michaelis-Menten equation. As shown in Table 2, with TMB as substrate, the Michaelis constant (K m ) is smaller, indicating that it has a stronger affinity for the substrate TMB, and its K cat / K m It is about 8.43 times of Fe-N / OC SA. cat / K m The value is about 8.68 times that of HRP (natural peroxidase), indicating that its enzyme activity is comparable to that of the natural enzyme.

[0068] Fig.10 :The application effect of Fe-N / O / Cl-C in the degradation of malachite green is demonstrated. In sodium acetate buffer (pH 3.8), 2 mg of Fe-N / O / Cl-C was added to 50 mL of 10 mg·L-1 malachite green solution, and 5 mL of 30% H2O2 was added. The results showed that in the presence of H2O2 alone, the degradation rate of malachite green was 42.4%; when Fe-N / O / Cl-C was used alone, the removal rate was 68.9%; with the assistance of 3% H2O2, the degradation rate of malachite green reached 97.5% within 2.5 hours. The degradation process conforms to pseudo-first-order reaction kinetics, and the reaction rate constant is 2.5×10 -2 min -1 .

[0069] The above embodiments are preferred embodiments of the present invention, but they do not limit the embodiments of the present invention. Any changes, modifications, substitutions, combinations or simplifications made without departing from the spirit and principle of the present invention shall be regarded as equivalent replacements and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a single-atom nanozyme based on planar and axial coordination design, characterized in that: The following steps are involved: (1) dispersing melamine, cyanuric acid, L-alanine and phytic acid in water, heating and stirring, adding iron salt, and freeze-drying to obtain a precursor; (2) taking the precursor obtained in step (1), heating it to a pyrolysis temperature, cooling it, taking out the powder and grinding it to obtain Fe-N / O-CSA; the pyrolysis temperature is 500 to 800°C; (3) The Fe-N / O-C SA obtained in step (2) is dispersed in an aqueous solution of HCl, heated and stirred, filtered and washed, the precipitate is collected, and dried to obtain the single-atom nanozyme Fe-N / O / Cl-CSA.

2. According to claim 1, a method for preparing a single-atom nanozyme based on planar and axial coordination design, characterized in that: The mass ratio of melamine, cyanuric acid, L-alanine and phytic acid in step (1) is 1:1:1:(0.05-0.2); the ratio of iron ions in the iron salt to L-alanine is 1 mmol:1 g.

3. According to claim 2, a method for preparing a single-atom nanozyme based on planar and axial coordination design, characterized in that: The iron salt in step (1) is at least one of Fe(NO3)3, Fe(NO3)3·9H2O, FeCl2, and FeCl3.

4. According to claim 3, a method for preparing a single-atom nanozyme based on planar and axial coordination design is characterized in that: The stirring temperature in step (1) is 50-200° C., the stirring speed is 400-800 rpm, and the time is 2-14 hours; the freeze-drying conditions are -40-60° C., 0-10 Pa, and 30-60 hours.

5. The method for preparing a single-atom nanozyme based on planar and axial coordination design according to claim 4, characterized in that: The pyrolysis in step (2) is carried out in an inert gas atmosphere, the pyrolysis temperature is 700±50°C, the heating rate is 5±3°C / min, and the pyrolysis time is not less than 2 hours.

6. The method for preparing a single-atom nanozyme based on planar and axial coordination design according to claim 5, characterized in that: The concentration of the HCl aqueous solution in step (3) is 1 to 4 M, the stirring temperature is 40 to 80° C., and the stirring time is 1 to 24 hours.

7. The single-atom nanozyme prepared by the method according to any one of claims 1 to 6.

8. Use of the single-atom nanozyme according to claim 7 in dye degradation.

9. The use according to claim 8, characterized in that: The method comprises the following steps: mixing Fe-N / O / Cl-C SA and dye in a mass ratio of (1-10):1, and performing degradation reaction in a 1-10% H2O2 environment.

10. The use according to claim 9, characterized in that: The dye is one or more of malachite green, methyl orange, methylene blue and rhodamine B; the degradation reaction is carried out at pH 2-5 and room temperature.